A Case of Vaping-associated Acute Lung Injury. Issue 3 (31st May 2020) - Rasmussen, Cory; Balachandran Nair, Girish; Al-Katib, Sayf
Abstract : Although vaping has been promoted by manufacturers as a safe alternative to traditional smoking, the dangers of vaping and e-cigarette use have come to the forefront of the medical community, particularly the risks associated with tetrahydrocannabinol-containing products. Although many patterns of vaping-associated lung injuries have been reported in the literature, one of the most concerning is that of diffuse alveolar damage. As e-cigarette and vaping use is becoming increasingly popular, particularly in the younger population, it is important to become familiar with this entity to ensure proper and timely diagnosis to prevent lifelong sequelae.